2020
DOI: 10.2147/rmhp.s264943
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Study of Out-of-pocket Payment and the Exposure of Households with Catastrophic Health Expenditures Following the Health Transformation Plan in Iran</p>

Abstract: Introduction: One of the main objectives of health systems is providing financial protection against out-of-pocket (OOP) health expenditures. According to the 2011 report by the World Health Organization in the Eastern Mediterranean Regional Office (EMRO), a huge portion of health service in Iran is paid OOP, which is around 58% of the total health system expenditure. Furthermore, all over the world, around 25 million households (100 million people) are trapped in poverty as a result of paying health service c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 18 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…Studies have shown that considerable dependence on out-of-pocket payments (OOP) as the most important source of payment for medical needs not only has an inauspicious consequence on demand for services, but also represents an increasing financial problem among families, leading to deprivation [3,4]. In addition, existing studies have indicated that per capita income expenditure on health and welfare in many low-and middle-income countries is likely to increase quickly in the long run [5,6]. Moreover, the prevention of extremely harmful health disbursements and the necessity to strive towards universal health coverage have drawn the attention of governments and several stakeholders to provide health insurance schemes that will offer subsidized fees and healthcare accessibility to citizens, especially in developing countries such as Nigeria and South Africa [3,4].…”
Section: Introduction/backgroundmentioning
confidence: 99%
“…Studies have shown that considerable dependence on out-of-pocket payments (OOP) as the most important source of payment for medical needs not only has an inauspicious consequence on demand for services, but also represents an increasing financial problem among families, leading to deprivation [3,4]. In addition, existing studies have indicated that per capita income expenditure on health and welfare in many low-and middle-income countries is likely to increase quickly in the long run [5,6]. Moreover, the prevention of extremely harmful health disbursements and the necessity to strive towards universal health coverage have drawn the attention of governments and several stakeholders to provide health insurance schemes that will offer subsidized fees and healthcare accessibility to citizens, especially in developing countries such as Nigeria and South Africa [3,4].…”
Section: Introduction/backgroundmentioning
confidence: 99%
“…This has important policy implications for health transformation plan in developing countries aimed at reducing catastrophic health expenditures and reducing the incidence of poverty due to disease. 51 …”
Section: Discussionmentioning
confidence: 99%
“…The HTP in Iran is closely tied to the goal of achieving UHC for the population [ 26 ]. The HTP has made significant strides towards achieving UHC by expanding health insurance coverage, increasing the number of healthcare facilities, and improving the quality of healthcare services [ 27 ]. Expanding health insurance coverage has been a crucial component of the health transformation plan [ 28 ].…”
Section: Main Textmentioning
confidence: 99%